THE EFFECT OF ROLE PLAY FOR ENGLISH STUDENTS SPEAKING IN JUNIOR HIGH SCHOOL OF SMP MUHAMMADIYAH 11 SUKODADI - Aini, Firda Fadhila; Anwar, Khoirul; Asmara, Candra Hadi (Journal of English Teaching, Literature, and Applied Linguistics, 2020)
Role play is a method of acting out particular ways of behaving or pretending to be other people who deal with new situations. Role play is very important in teaching speaking because it gives students an opportunity to practice communicating in different social contexts and in different social roles. The purpose of this study is to find out the significant effect on students fluency in speaking skills taught by using Role Play for students in Junior High School. The researcher used an experimental design in which there are two classes; one of the experiment group and the control group that each has 20 students. The data is collected through quantitative methods. The quantitative data is obtained from the result of the pre-test and post-test students speaking skills. Before implement Role Play, students had to take pre-test to identify their speaking ability. One group practice a dialogue in pair use Role Play strategy about greeting, leave taking, thanking and apologizing expressions. Other group was asked to practice a dialogue used drilling strategy. Both groups were tested for their oral production and competence. After the presentation, the post-test was used to find out whether there was a significant effect using Role Play in speaking ability. The implementation of Role Play and Drilling showed that students who are though used Role Play in teaching speaking can improve their speaking skill especially in fluency.